Fluids Along the Plate Interface Influencing the Frictional Regime of the Chilean Subduction Zone, Northern Chile. Issue 19 (11th October 2018) - Pasten‐Araya, F.; Salazar, P.; Ruiz, S.; Rivera, E.; Potin, B.; Maksymowicz, A.; Torres, E.; Villarroel, J.; Cruz, E.; Valenzuela, J.; Jaldín, D.; González, G.; et al.
Abstract: The plate interface beneath the Mejillones Peninsula in Northern Chile is characterized by anomalous seismogenic behaviors, with seismic and aseismic slip, and low coupling values. We analyze this zone through the seismicity pattern and a 3‐D tomography model. We identify high V P / V S values within the oceanic crust and in the lower continental crust, which we interpret as hydrated zones rich in fluids. These zones are correlated with the Mejillones fracture zone and with highly permeable lithologies of the lower continental crust, which allow a greater accumulation of fluids at the plate interface beneath the Mejillones Peninsula. Additionally, these areas exhibit a high rate of seismicity and concentrated swarms and repeaters. We propose that the presence of fluids controls the anomalous seismogenic behavior along the plate interface beneath the Mejillones Peninsula. Plain Language Summary: The interplate zone beneath Mejillones Peninsula (MP), northern Chile, presents an anomalous seismogenic behavior with aseismic pulses, low coupling values, and acting as a seismic barrier for earthquakes occurred in adjacent areas. We believe that this anomalous behavior is due to the presence of fluids in the interplate zone under the MP. To corroborate this, we study the seismicity recorded by a local seismological network and constructed a tomographic velocity model. Our results show that within the oceanic crust and in the lower continental crust exist the presence of fluids that concentrates to the north and center of the MP, which correlate with the presence of the Mejillones fracture zone and with more fractured and permeable lithologies of the continental crust. This situation changes to the south of the MP where fluid concentration is lower. This is the first detailed attempt to characterize the role of fluids in the rheology of barriers within subduction zones and to distinguish geological controls on the fluid distribution. We believe that this type of study is fundamental for facilitating future prospective analysis of earthquake distributions and conducting hazard assessments. Key Points: The Mejillones Peninsula presents variability in the distributions of seismicity, swarms, and repeaters High V P / V S values indicate zones rich in fluids, correlated with the Mejillones fracture zone and permeable lithologies Areas rich in fluids control the seismogenic behavior of the plate interface beneath the Mejillones Peninsula